Ofertas da plataforma Telessaúde no Brasil: como estamos? - Siyoufi, Carolina Tuma Khouri (2024)
The Telehealth Brazil Networks Program (TBNP), established in 2007, seeks to integrate teaching and teleconsulting services, formative second opinion, tele diagnosis and tele-education through information and communication technologies. It aims to improve the quality of primary health care through Telehealth Centers (TCs) within Brazilian states. With the objective of identifying, describing, analyzing and comparing the TCs, this study used information from the Virtual Health Library (https://aps.bvs.br/rede-de-colaboradores/) and social networks, accessed between 14/06/23 and 17/09/23. The data showed that 74% of the 28 TCs are active, with only 22% offering all the services provided. Teleconsulting showed a significant increase (739%; 2013 to 2020) and is offered by 94% of the TCs. Only the Rio Grande do Sul TC provides free access; it is the TC with the highest number of teleconsultations (23,832/year; 2013 to 2020). The percentage of referrals avoided, available only in the Minas Gerais TC, was 74% by August 2023. There is great heterogeneity in the presentation of offers and performance data between the TCs. It is concluded that TBNP has flaws, analyzed according to Donabedian’s classifications for the quality of health systems, at the levels of structure (conformation of sites, system operation), process (interaction with the population assisted) and results (changes in indicators and behaviors and referrals avoided). The TCs need to be standardized and updated to help improve services, adherence and use of the activities on offer, as well as the presentation of indicators proving that the programme's objectives have been achieved. The government's commitment to keeping the program in continuous operation and with the necessary quality is still a crucial point. This is what we hope for in the not-too-distant future